Pengembangan E-Modul Pemisahan Senyawa Fenolik dari Fraksi Simpur Air dengan Teknik Kromatografi Lapis Tipis (KLT) Preparatif Sebagai Sumber Belajar Kimia Bahan Alam - Ersando Ersando; Rini Muharini; Ira Lestari; Rody Putra Sartika; Rahmat Rasmawan (Universitas Pendidikan Mandalika Mataram, 2022)
The purpose of this study was to determine the E-Module of Natural Materials Chemistry based on a flipbook application with the material for Separation of Phenolic Compounds from the Simpur Air (Dillenia suffruticosa) Fraction using a preparative Thin Layer Chromatography (TLC) technique. The research method used is a research and development method by applying the ADDIE model. The subject of this research is the E-module for Separation of Phenolic Compounds from the Simpur Air (D. Suffruticosa) Fraction using Preparative Thin Layer Chromatography (TLC). The research instrument used was assessment and data analysis using a Likert scale. The data collection technique used is an indirect communication technique by giving a questionnaire. The feasibility of the E-module was assessed by two material experts, three media experts, and two linguists. The final results are seen in the material aspect which is obtained 100%, the media aspect is obtained 100%, and the language aspect is obtained 100%. Thus, it can be locked that the E-Module of Natural Materials Chemistry based on a flipbook application with the material for Separation of Phenolic Compounds from the Simpur Air (D. suffruticosa) Fraction Using a preparative Thin Layer Chromatography (TLC) technique is very feasible.